Effect of the fatigue on the physical performance in different small-sided games in elite football players - Pellegrino, G. C.; Paredes-Hernández, V.; Sánchez-Sánchez, J.; Garcia-Unanue, J.; Gallardo, L. (The Journal of Strength and Conditioning Research, 2020)
Football players need to be able to perform high-intensity efforts of short duration with brief recovery periods. The aim of this study was to analyze the influence of the pitch dimension on high-intensity actions and the effect of a repeated sprint ability (RSA) test on the physical performance in different 4-against-4 (4v4) small-sided games (SSG) dimensions. Sixteen U-18 elite football players performed an RSA test between two 4v4 SSGs (pre and post) to induce fatigue and compare physical data. Speed, sprint number, accelerations, sprint distance, total distance covered, and total distance covered of the players at different intensities were evaluated in 3 different SSGs (125, 150, 250, and 300 m2). Results revealed a significant detriment of physical performance in the 125-m2 SSG after RSA, mostly in number of sprints (-6.56; confidence interval [CI] 95%: -10.13 to -3.00; effect size [ES]: 1.13 p < 0.001), accelerations (-2.69; CI 95%: -5.13 to -0.24; ES: 0.68; p = 0.032), and sprint distance (-65.44 m; CI 95%: -103.73 to -27.16; ES: 1.20; p = 0.001). In bigger SSGs (250 and 300 m2), higher distance at high intensity was covered and Vmax, Vmean, and sprint distance were greater. In summary, accelerations, sprint number, and fatigue were higher in smaller pitches, and higher velocities were reached in bigger SSGs. Football players should be aware that changes in pitch size can modify the physical performance on high-intensity actions in SSGs.